Implementasi Algoritme Stream Cipher Grain-128A dan Shamir's Secret Sharing pada Sistem Arsip Data Kependudukan - Dita Nurina Malinda; Ari Kusyanti; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Personal data of resident is a data that must be stored and protected by the state. Due to the increasing number of data theft, we need to know that there are many things that can be done if an individual controls other people's ID card data, it can be used to deceive or even rob money from other people's bank accounts (Witjaksono, 2018). The way to overcome this problems is to use a cryptographic algorithm as a security for the population data archive system to ensure security in terms of integrity and authentication. This study describes the design, implementation and performance of a web-based population data archive system that utilizes the Grain-128a algorithm to ensure confidentiality and integrity with additional authentication. In addition, Shamir's Secret Sharing is also added as additional security. The tests carried out in this study included testing the performance of the Grain-128a algorithm in terms of keystream generation time, encryption and decryption as well as the performance of the Shamir's Secret Sharing algorithm in splitting and reconstructing data. As for security testing, using sniffing, brute force, birthday attacks and black box checking. The results showed that the keystream and authentication tags generated by the system were in accordance with the test vector. The result of the test is that the average time to generate a keystream is 7.8 microseconds. Meanwhile, the time to perform encryption and decryption using the Grain-128a algorithm is 10.1 microseconds and 8.3 microseconds. The test results with brute force experiments showed good results because from the attack the keystream of the Grain-128a algorithm could not be known. Tests with a birthday attack show that the authentication tag used in the population data archive system is safe because the attacker failed to find 2 tags with the same value. The test results using black box indicate that the population data archive system has been running well and in accordance with system requirements both functionally and non-functionally.